Application of Green Architecture Principles in Umbulan Pasuruan Natural Tourism Design - Krisnawangseh, Afni; Mutiara, Elok; Bahar, Mohammad Arsyad (Proceedings of the International Conference on Green Technology; Vol 10 (2019): Proceeding of International Conference on Green Technology, 2020)
Green architecture is an architecture that consumes natural resources, including energy, water, and material, and minimizes negative impacts on the environment. Green architecture is a step to realize sustainable human life. Green architecture has 3 main principles, namely: energy savings, utilization of renewable energy and the use of local materials. Of the three principles above, it will be applied to pennant natural tourism. Natural tourism is a form of recreation and tourism that utilizes the potential of natural resources, namely a source of water, both in natural conditions and after cultivation, allowing tourists to get physical and spiritual freshness, gain knowledge and experience, and grow inspiration and love for nature.